2007
DOI: 10.1016/j.ecss.2006.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Hiding and feeding in floating seaweed: Floating seaweed clumps as possible refuges or feeding grounds for fishes

Abstract: Paper in pressVandendriessche S., Messiaen M., O'Flynn S., Vincx M., Degraer S.Hiding and feeding in floating seaweed: floating seaweed clumps as possible refuges or feeding grounds for fishes ABSTRACTFloating seaweed is considered to be an important habitat for juvenile fishes due to the provision of food, shelter, a visual orientation point and passive transport. The importance of the presence of the highly dynamical seaweed clumps from the North Sea to juvenile neustonic fishes was investigated by analysin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 33 publications
1
39
0
Order By: Relevance
“…Ingolfsson and Kristjansson (2002) found that only 28 % of 1482 juvenile lumpfish collected in June-September had food in their stomachs, whereas 27 % of the juveniles in the same study had remains of food in their stomach. This may indicate a rapid degradation of prey in juvenile lumpfish, as a study by Vandendriessche et al (2007) observed food in all stomachs, also in winter.…”
Section: Effect Of Temperature On Feed Related Parametersmentioning
confidence: 98%
See 1 more Smart Citation
“…Ingolfsson and Kristjansson (2002) found that only 28 % of 1482 juvenile lumpfish collected in June-September had food in their stomachs, whereas 27 % of the juveniles in the same study had remains of food in their stomach. This may indicate a rapid degradation of prey in juvenile lumpfish, as a study by Vandendriessche et al (2007) observed food in all stomachs, also in winter.…”
Section: Effect Of Temperature On Feed Related Parametersmentioning
confidence: 98%
“…Juvenile lumpfish feed throughout the year (Vandendriessche et al 2007). Small juvenile lumpfish with yolk sacks are found to feed on small crustaceans (harpacticoid copepods) before shifting to amphipods (Callopius laeciusculus and Parathemisto gaudichaudi) with increasing size (Daborn & Gregory 1983;Ingolfsson & Kristjansson 2002).…”
Section: Effect Of Temperature On Feed Related Parametersmentioning
confidence: 99%
“…Previous algal studies have used patch sizes ranging from a single algal thallus to greater than 100 g (Roberts and Poore, 2005;Christie et al, 2007;Vandendriessche et al, 2007a;Christie et al, 2009;Jobe and Brooks, 2009). Habitat sizes of either 20 g 6 0.5 g or 30 g 6 0.5 g were used for habitat selection experiments.…”
Section: Methodsmentioning
confidence: 99%
“…attract and concentrate fauna (Hunter and Mitchell, 1968;Kingsford, 1995;Lapointe, 1995;Ingólfsson, 1998;Casazza and Ross, 2008) by increasing the complexity of the pelagic environment (Kingsford, 1995;Ingólfsson, 1998). Generally, the fish community is more diverse and abundant below floating seaweeds than below other floating items (Dooley, 1972;Fedoryako, 1989;Lapointe, 1995;Vandendriessche et al, 2007a). Adrift alga is also important as a dispersal agent for nearshore fauna (Helmuth et al, 1994;Parker and Tunnicliffe, 1994;Ingólfsson, 1995Ingólfsson, , 1998.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation